UNIEVANGÉLICA ITINERANT CITIZEN - FACEG GOIANÉSIA (CIPEEX, 2022)
THE UNIEVANGLICA CITIZEN ITINERANT PROJECT - FACEGGOIANSIA CONSISTED OF A PARTNERSHIP BETWEEN THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGLICA AND THE FACULDADE EVANGÉLICA DE GOIANSIA, HELD ON JUNE 16, 2018. ITS PURPOSE WAS TO IMPROVE THE QUALITY OF LIFE OF THE POPULATION OF A GIVEN LOCATION THROUGH THE EFFICIENT EXECUTION OF THE PROPOSED ACTIONS. IT PROMOTED, DIRECTLY OR INDIRECTLY, THE INTERVENTION IN THE SOCIAL, CULTURAL, ENVIRONMENTAL ASPECTS, BESIDES PROPITIATING THE EMPOWERMENT OF THE INDIVIDUALS IN RELATION TO THE HEALTH. THIS PROJECT IS OF GREAT RELEVANCE SINCE IT WAS THE INITIAL MARK OF DENTAL CARE PERFORMED AT THE RECENT INSTITUTION, WITH THE INAUGURATION OF THE TEACHING DENTAL CLINIC OF THE EVANGELICAL FACULTY OF GOIANSIA. THE OBJECTIVE OF THIS WORK IS TO DESCRIBE THE EXPERIENCES OF THE UNIVERSITY OF ANÁPOLIS - UNIEVANGLICA'S ACADEMICS AND TO PRESENT THE INITIATIVE OF THE INSTITUTION TO PROMOTE THE RAPPROCHEMENT BETWEEN STUDENTS FROM THE ANÁPOLIS AND GOIANSIA CAMPUSES. IN ALL, FIFTEEN ACADEMICS FROM THE 5TH TO THE 7TH PERIOD AND TWO PROFESSORS FROM THE UNIVERSITY CENTER OF ANÁPOLIS, BESIDES THE SCHOLARS OF THE 1ST PERIOD AND PROFESSORS FROM THE EVANGELICAL FACULTY OF GOIANSIA, CONTRIBUTED TO THE REALIZATION OF THE PROJECT. IN ALL, 45 DENTAL APPOINTMENTS WERE CARRIED OUT, ENCOMPASSING THE AREAS OF PERIODONTICS, DENTISTRY AND ORAL SURGERY, AS WELL AS ORAL HYGIENE INSTRUCTION ACTIVITIES. THROUGH THE COMMITMENT AND DEDICATION OF ACADEMICS, A HUMANE AND QUALITY SERVICE WAS OFFERED TO THE POPULATION. THE ASSOCIATION BETWEEN THE DIFFERENT CAMPUSES FOR THE WELL BEING OF THE COMMUNITY WAS ABLE TO PRODUCE A POSITIVE IMPACT ON THE LIVED REALITY AND TO CONTRIBUTE TO THE FORMATION OF HUMAN RESOURCES IN DENTISTRY, AWAKENING SOCIAL RESPONSIBILITY THROUGH THE EXTENSIONIST ACTIVITY.&NBSP;PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): EXTENSION. DENTISTRY. HEALTH PROMOTION.